Dandelion-shaped manganese sulfide in ether-based electrolyte for enhanced performance sodium-ion batteries. Issue 1 (December 2018) - Pham, Duong; Sambandam, Balaji; Kim, Sungjin; Jo, Jeonggeun; Kim, Seokhun; Park, Sohyun; Mathew, Vinod; Sun, Yang-Kook; Kim, Kwangho; Kim, Jaekook
Abstract Metal sulfide materials serve as environment-friendly, sustainable, and effective electrode materials for green-energy storage systems. However, their capacity-fading issues related to low electrical conductivity and drastic volume changes during electrochemical cycling have generally limited their application to sodium ion batteries. Here we show that with the combination of an ether-based NaPF6 /diglyme electrolyte, the dandelion-shaped manganese sulfide electrode displays enhanced reversible capacity, cycle life, and rate capability. The capacity of 340 mAh g−1 is maintained over more than 1000 cycles at a current density of 5.0 A g−1 . Furthermore, discharge capacities of 277 and 230 mAh g−1 at 10 and 20 A g−1 current densities, respectively, are obtained. Our work demonstrates the formation of a protective solid electrolyte interface layer along the surface of the primary seed particle that limits polysulfide dissolution and hence the preservation of the active material during reaction with sodium. Metal sulfide batteries suffer from low electrical conductivity which limits their application in sodium ion batteries. Here, the authors report a manganese sulfide anode in sodium ion batteries with capacity of 340 mAh g−1 maintained over more than 1000 cycles at a current density of 5.0 A g−1 .